Online optimized hysteresis-based steering feel model for steer-by-wire systems - Kirli, Ahmet; Arslan, Mehmet Selcuk (SAGE PUBLICATIONS LTD, 2016)
In rubber-wheeled road vehicles, the mechanical connection between steering wheel and front wheels provides steering-related feedback to the driver. The torque fed back to the driver through the steering linkages and steering wheel, which is called steering feel, helps the driver in controlling the vehicle. The torque feedback is reproduced via artificial methods in steer-by-wire systems due to the lack of mechanical connection. In this work, in order to minimize the physical workload and the lateral acceleration under the consideration of handling performance, optimization of a hysteresis-based steering feel has been studied. A 2-degree-of-freedom bicycle model based on the magic formula tire model has been used for simulations and hardware-in-the-loop experiments. A mathematical model is proposed in order to create an adaptive model-based optimization of the hysteresis parameters simultaneously while driving. A hardware-in-the-loop experimental setup has been used for the driving tests. The weave and the double-lane change tests have been performed with different drivers in order to demonstrate and quantify the optimization methods that are presented in this work.
Keywords: Steering feel; steer-by-wire; hysteresis; physical workload; online optimization; SIMULATION; VEHICLE; Thermodynamics; Engineering